Pengambilan Keputusan Alumni SMKN 2 Pekanbaru Tahun Ajaran 2023-2024 - Islah Oktaviani; Achmad Hidir (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This research uses a descriptive quantitative method, which aims to examine the decision making made by SMKN 2 Pekanbaru alumni in the 2023-2024 academic year after completing their education, this research identifies factors that influence their choices, such as continuing their education at a higher level, working, getting married, or entrepreneurship. Data were collected through questionnaires and analyzed using descriptive statistics. The results of this study illustrate that alumni decisions are strongly influenced by internal factors, such as self-confidence and academic ability, as well as external factors, such as family support and the influence of the social environment. It can be concluded that individual resources, social norms, and family support play an important role in the decision-making process, which can be the basis for improving the effectiveness of guidance programs in the future.